Preparation of Polymer Supported Phosphine Ligands by Metal Catalyzed Living Radical Copolymerization and Their Application to Hydroformylation Catalysis. Issue 5 (30th January 2013) - Cardozo, Andrés F.; Manoury, Eric; Julcour, Carine; Blanco, Jean‐François; Delmas, Henri; Gayet, Florence; Poli, Rinaldo
Abstract A series of well‐defined polystyrene‐supported tertiary phosphine ligands were prepared by copper‐catalyzed atom transfer radical polymerization (ATRP), involving direct copolymerization of styrene and 4‐diphenylphosphinostyrene (or 4‐styryldiphenylphosphine, SDPP). Copolymerization of the two monomers at different molar ratios showed a decreasing level of control as the SDPP molar fraction (fSDPP) increased. A satisfactory level of control was achieved for fSDPP≤0.25 such that there was a constant concentration of growing "living chains", and linear Mn growth with conversion and low dispersity. Copper‐free polymers with different chain lengths were prepared and tested as polymeric ligands in the rhodium‐catalyzed hydroformylation of 1‐octene. The polymeric ligands yielded higher linear/branched selectivity and lower activity relative to PPh3 at the same P/Rh ratio. The selectivity increased slightly as a function of the polymer chain length.